PREVIOUS EXPERIENCE OF UNIVERSITY STUDENTS IN PHYSICAL EDUCATION AT HIGH SCHOOL - Šišlova, Eleonora; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Students in Latvia have a moderately positive attitude towards organized physical activity at the university, it has been formed in the past and is related to the previous experience in physical education gained at school. To promote student involvement in physical activities and changes in students’ attitude towards physical activity at the university, it is necessary to evaluate their previous experience in physical education acquired at school. The aim of the study is to evaluate of the psychometric properties of the Youth Experiences Survey for Sport (YES-S) (MacDonald et.al., 2012) for students of Latvia. Research methods: The Youth Experiences Survey for Sport (YES-S), Principal component factor analysis. Respondents: 265 students aged from 19 to 24 from four universities of Latvia. Some contradictions were identified between the theoretical basis of the YES-S instrument’s scale and the various criteria that can characterize experience in physical education. As a result, a five-factor structure was developed, which includes 19 items. The factor loads of the other 18 items indicated that these items were not compatible with the theoretical concept of the YES-S.